2019
DOI: 10.1002/cncy.22104
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and malignancy rates of indeterminate pediatric thyroid nodules

Abstract: Background The American Thyroid Association guidelines task force currently recommends definitive thyroidectomy or lobectomy after an indeterminate thyroid biopsy in children. This recommendation is based on evidence of a greater incidence and a higher risk of malignancy compared with adults in earlier pediatric studies. Such management may lead to overtreatment and unnecessary surgery for many children in the United States. Methods The objective of the current study was to re‐evaluate pediatric thyroid nodule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 36 publications
5
41
1
2
Order By: Relevance
“…Although there is significant variability between studies, the risk of malignancy in non-diagnostic (Bethesda I), benign (Bethesda II), and suspicious/malignant (Bethesda V/VI) mirror adult risk assessment at 0% (range 0–10%), 5–8% (range 0–16%), and 100% respectively (Bethesda V range: 40–100%, Bethesda VI range: 100%). [42]. Several studies suggest that Bethesda III (atypia of uncertain significance/follicular lesion of uncertain significance; AUS/FLUS) and Bethesda IV (follicular neoplasm/suspicious for follicular neoplasm; FN/SFN) categories account for up to 40% (range: 13–43%) of all pediatric FNA diagnoses [42].…”
Section: Pathologic Evaluationmentioning
confidence: 99%
See 3 more Smart Citations
“…Although there is significant variability between studies, the risk of malignancy in non-diagnostic (Bethesda I), benign (Bethesda II), and suspicious/malignant (Bethesda V/VI) mirror adult risk assessment at 0% (range 0–10%), 5–8% (range 0–16%), and 100% respectively (Bethesda V range: 40–100%, Bethesda VI range: 100%). [42]. Several studies suggest that Bethesda III (atypia of uncertain significance/follicular lesion of uncertain significance; AUS/FLUS) and Bethesda IV (follicular neoplasm/suspicious for follicular neoplasm; FN/SFN) categories account for up to 40% (range: 13–43%) of all pediatric FNA diagnoses [42].…”
Section: Pathologic Evaluationmentioning
confidence: 99%
“…[42]. Several studies suggest that Bethesda III (atypia of uncertain significance/follicular lesion of uncertain significance; AUS/FLUS) and Bethesda IV (follicular neoplasm/suspicious for follicular neoplasm; FN/SFN) categories account for up to 40% (range: 13–43%) of all pediatric FNA diagnoses [42]. Further, these indeterminate aspirate diagnoses are associated with increased risk of malignancy in children versus adults (28% in children vs. 6–30% in adults for AUS/FLUS and 58% in children vs. 10–40% in adults for FN/SFN lesions) [42].…”
Section: Pathologic Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…For the adult population, some Italian Authors have studied national cohorts affected by thyroid nodules and reported signi cantly higher sensitivity of the Italian system than the Bethesda one, validating the TIRa/TIR3b subclassi cation for the individuation of benign nodules and malignant tumors, with a rate of malignancy of 4-20.8% and 28-60.3%, respectively [33][34][35][36][37][38][39][40][41][42][43][44]. Pediatric studies based on the BSRTC system indicate a higher ROM for indeterminate nodules (39.5% for AUS/FLUS category and 41.5% for the SFN category) compared to adults (30.5% and 28.9% respectively), with no substantial differences in ROM between the two indeterminate categories in both pediatric and adult age [46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%